(untitled) (Chemical Engineering Research Bulletin, 2008)
This study compares the quality of different brands of Ordinary Portland Cement (OPC) available in Bangladesh. The amounts of chemical constituents like SiO2, Al2O3, Fe2O3, CaO, MgO, SO3, insoluble residue (IR), free lime and loss on ignition (LOI) were determined in accordance with British Standard (BS) Specifications. All the results are presented to provide both quantitative and qualitative notion of several locally produced ordinary Compositions of most of this constituents as determined experimentally were within the range of the standard values. The possible reasons for variation in chemical compositions and their consequences have been discussed. Keywords: Ordinary Portland Cement, Chemical Composition, Quality Verification. DOI = 10.3329/cerb.v12i0.1491 Chemical Engineering Research Bulletin 12 (2008) 7-10